Optimization of a portable liquid scintillation counting device for determining 222Rn in water. (October 2018) - Celaya, Santiago; Fuente, Ismael; Quindós, Luis; Sainz, Carlos
Abstract: The new EU Council Directive 2013/51/Euratom of 22 October 2013 introduced limits for the content of 222 Rn in drinking water. Radon analysis in water requires a lengthy task of collection, storage, transport and subsequent measurement in a laboratory. A portable liquid scintillation counting device allows rapid sampling with significant savings of time, space, and cost compared with the commonly used techniques of gamma spectrometry or methods based on the desorption of radon dissolved in water. In this study, we describe a calibration procedure for a portable liquid scintillation counting device that allows measurements of 222 Rn in water by the direct method, and we also consider the case of 226 Ra being present in the sample. The results obtained with this portable device are compared with those obtained by standard laboratory techniques (gamma spectrometry with a high-purity Ge detector, gamma spectrometry with a NaI detector, and desorption followed by ionization chamber detection). Graphical abstract: Image 1 Highlights: Calibration of a portable LSC device for radon measurements in water by the direct method. Interference of 210 Po in samples with 226 Ra when the direct method is used. Use of the portable LSC device versus standard laboratory techniques (gamma spectrometry and desorption).